Is There an Anti-Jewish Bias in Today's University? - Rosenfeld, Alvin H. 1938- (2022)
In “Is There an Anti-Jewish Bias in Today’s University?,” Alvin H. Rosenfeld maintains that contemporary American universities, like the surrounding cultures in which they exist, are not free of new adaptations of the “Jewish question.” While clearly recognizing that no one is calling for a “final solution,” he argues that certain recent campus developments are troubling all the same. Some of the troubles relate to changing attitudes toward how the victims and perpetrators of the Nazi Final Solution of the Jewish Question should be remembered, including how they should be presented in university level teaching and research. In some quarters, one observes feelings of impatience with Holocaust memory and resentment towards Jews for keeping such memory alive. In addition, some universities have seen the emergence of an intensely negative, aggressively hostile attitude toward Israel and its supporters, which expresses itself in well-organized Boycott, Divestment, and Sanctions Movement (BDS) programs, annual Israel Apartheid weeks, and other campus manifestations of anti-Israel activity. Taken together, these developments have made a number of American university campuses no longer seem as hospitable to Jewish students and others as they once were. In the context of current debates both within Europe and North America about immigration and the status of refugees, such developments—with their inevitable echoes of a dark past—emerge as all the more troubling.
Keywords: Antisemitism; Holocaust; Shoah; Jewish Studies; National Socialism; Nazi biblical scholarship; Antisemitismus; Entwicklung; Antizionismus; Juden, Drittes Reich; Universität; Geisteswissenschaften; Nationalsozialismus; Boycott, Divestment and Sanctions (BDS) Movement; Judenvernichtung